Initial analysis of the impact of the Ukrainian power grid synchronization with Continental Europe. (9th December 2022) - Böttcher, Philipp C.; Rydin Gorjão, Leonardo; Beck, Christian; Jumar, Richard; Maass, Heiko; Hagenmeyer, Veit; Witthaut, Dirk; Schäfer, Benjamin
Abstract : Following the Russian invasion of Ukraine in February 2022, the Ukrainian power grid was synchronized to the Continential Euopean grid. We show how power flows changed, while frequency statistics remained almost unchanged. Abstract : When Russia invaded Ukraine on the 24th of February 2022, this led to many acts of solidarity with Ukraine, including support for its electricity system. Just 20 days after the invasion started, the Ukrainian and Moldovan power grids were synchronized to the Continental European power grid to provide stability to these grids. Here, we present an initial analysis of how this synchronization affected the statistics of the power grid frequency and cross-border flows of electric power within Continental Europe. We observe faster inter-area oscillations, an increase in fluctuations and changes in the cross-border flows in and out of Ukraine and surrounding countries as an effect of the synchronization with Continental Europe. Overall these changes are small such that the now connected system can be considered as stable as before the synchronization.